A SABBATICAL YEAR IN PUBLIC ACCOUNTING. - Dickens, Robert L. (The Accounting Review, 1956)
Abstract This article focuses on the author's personal experience about a sabbatical fellowship program. The author who is assistant professor at the Duke University, says, that the termination of a one-year fellowship program in public accounting with the firm Price Waterhouse & Co., has proven most interesting and valuable. Returning to the classroom after a year of study and work with an accounting firm has emphasized the benefits of such a program to the teacher and his students. Since the fellowship was arranged for my sabbatical leave, a period of one year, it necessarily took on many of the attributes of regular employment, my assignments including regular staff work on various audits performed by the firm. Thus, instead of being merely an observer on these audits, my position was more nearly that of a member of the staff. As shall be explained subsequently, there were certain features of this fellowship which distinguish it from regular employment and thus made it possible to gain a maximum benefit from a relatively short period of experience.